Analysis Of The Influence Of Work Productivity, Work Environment And Workload On Performance Of Ministry Office Employees - Fatkhuri Fatkhuri; Muhamad Risal Tawil; Hisarma Saragih; Esi Sriyanti; Afni Yeni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
The purpose of this study is to determine and examine how employee performance in one of Ministry in Indonesia is impacted by the physical work environment, workload, and productivity. 100 respondents were included in the saturation sampling approach used to select the research sample. With the use of SPSS software version 26, multiple linear regression techniques were used to analyze the data for this investigation. The findings demonstrated that employee performance was impacted by the physical work environment, workload, and productivity all at the same time. With a significance value of 0.000, the physical work environment has a considerable impact on employee performance to some extent. Employee performance is also significantly impacted by workload, and employee performance is significantly impacted by work productivity. In the coefficient of determination (R2), the corrected R Square value shows that all independent variables simultaneously has positive and significant effect on performance of employees in ministry office.